Preliminary study of an oral vaccine against infectious hematopoietic necrosis virus using improved yeast surface display technology. (May 2017) - Zhao, Jing-Zhuang; Xu, Li-Ming; Liu, Miao; Cao, Yong-Sheng; LaPatra, Scott E.; Yin, Jia-Sheng; Liu, Hong-Bai; Lu, Tong-Yan
Highlights: Preliminary study of an oral vaccine against infectious hematopoietic necrosis virus. The oral vaccine was designed using improved yeast surface display technology. The yeast oral vaccine induced an efficient mucosal immune response. It can be used as primer or booster vaccination before or after DNA vaccination. Abstract: Infectious hematopoietic necrosis virus (IHNV) is a common pathogen that causes severe disease in the salmonid aquaculture industry. Because oral vaccines induce more efficient mucosal immunity than parenteral immunization, an oral vaccine was developed with an improved yeast cell surface display technology to induce an immune response to IHNV. The oral yeast vaccine, designated EBY100/pYD1-bi-G, was delivered orally to rainbow trout ( Oncorhynchus mykiss ) on days 1 and 32, and the nonspecific and specific immune responses were measured 50 days after the first vaccination. In the hindgut, spleen, and head kidney, the expression of IFN-1 and Mx-1 was significantly upregulated after oral vaccination with EBY100/pYD1-bi-G, and the highest expression of IFN-1 and Mx-1 was observed in the spleen (7.5-fold higher than the control group) and head kidney (3.9-fold higher than the control group), respectively. Several markers of the adaptive immune response (IgM, IgT, CD4, and CD8) were also significantly upregulated, and the highest expression of these markers was observed in the hindgut, suggesting that the mucosal immune response was successfully induced by oral vaccination with EBY100/pYD1-bi-G. Sera from the orally vaccinated rainbow trout showed higher anti-IHNV neutralizing antibody titers (antibody titer 81 ± 4) than the control sera (antibody titer 7 ± 3), and the relative percentage survival after IHNV challenge was 45.8% compared with 2% in the control group. Although the protection afforded by this orally delivered vaccine was lower than that of a DNA vaccine (83%–98%), it is a promising candidate vaccine with which to protect larval fish against IHNV, which are most susceptible to the virus and difficult to inject with a DNA vaccine.